The corruption of Legitimacy: How American and British Counterinsurgency Strategies Ignore Jus ad Bellum as the Foundation of Legitimate War - Tokarczyk, Andre (Université d'Ottawa | University of Ottawa, 2019)
The United States Army Field Manual FM 3-24 Insurgencies and Countering Insurgencies (FM 3-24) and the British Army Field Manual Volume 1 Part 10 Countering Insurgency (AFM 1-10) are the most comprehensive representations of modern counterinsurgency thinking. Yet they both contain several fundamental flaws that diminish their usefulness as effective strategic frameworks. American and British counterinsurgency strategies lack any significant discussion of the principles of just war theory, as a result they fundamentally misunderstand legitimacy in the context of war. FM 3-24 and AFM 1-10 forget that legitimacy is not a by-product of jus in bello alone, instead it is a result of satisfying all of criteria of jus ad bellum and of behaving justly in war (i.e. adhering to jus in bello). This paper argues that modern counterinsurgency frameworks would be better served if they incorporated the principles of jus ad bellum more rigorously. Incorporating all aspects of just war theory into counterinsurgency thinking would lead to better strategies that discourage overly aggressive interventions that cause unnecessary harm to soldiers and civilians alike.